(untitled) (Edad Media. Revista de Historia, 2026)
After the expulsion of the Jews ordered by the Catholic Monarchs in March 1492, those affected embarked on a painful journey in search of new places to settle, enduring all kinds of hardships and rejections. This led some of them to request permission from the monarchs to return, which was formalized with the promulgation of a new decree authorizing their return, contingent upon conversion, on November 10, 1492. In this study, we have sought to determine whether this phenomenon occurred in Valladolid and, if so, to analyse how this reintegration took place through the property claims made by returning converts, preserved in judicial rulings issued by the city’s courts.